Menstrual dysfunction in Hong Kong athletes - Chung, S.; Siu, P.-I. F. (Research Highlights, 2021)
The purpose was to investigate the prevalence of menstrual dysfunction, i.e. irregular cycle length, discomfort during menstruation, menstrual pain, in athletic and non-athletic Hong Kong females. Methodology: Fifty seven athletic females, recruited from the Hong Kong Sports Institute, and 42 non-athletic females, recruited from the universities, aged 18 - 30 years, were asked to fill out a questionnaire regarding their age at menarche, menstrual cycle length, discomfort during menstruation (i.e. fatigue, lower back pain, dizziness, nausea, vomiting), menstrual pain. Information like training years, decrease in training intensity during menstruation were also collected in the athletic female group.